Paeoniflorin alleviates 17α-ethinylestradiol-induced cholestasis via the farnesoid X receptor-mediated bile acid homeostasis signaling pathway in rats - Wang, Rulin; Yuan, Tengteng; Sun, Jing; Yang, Menghuan; Chen, Yunna; Wang, Lei; Wang, Yanyan; Chen, Weidong; Peng, Daiyin (Frontiers in Pharmacology, 2022)
Cholestasis, characterized by disturbance of bile formation, is a common pathological condition that can induce several serious liver diseases. As a kind of trigger, estrogen-induced cholestasis belongs to drug-induced cholestasis. Paeoniflorin is the most abundant bioactive constituent in Paeonia lactiflora Pall., Paeonia suffruticosa Andr., or Paeonia veitchii Lynch, a widely used herbal medicine for treating hepatic disease over centuries in China. However, the pharmacologic effect and mechanism of paeoniflorin on estrogen-induced cholestasis remain unclear. In this experiment, the pharmacological effect of paeoniflorin on EE-induced cholestasis in rats was evaluated comprehensively for the first time. Ultra-high performance liquid chromatography coupled with Q-Exactive orbitrap mass spectrometer was used to monitor the variation of bile acid levels and composition. It was demonstrated that paeoniflorin alleviated 17α-ethinylestradiol (EE)-induced cholestasis dose-dependently, characterized by a decrease of serum biochemical indexes, recovery of bile flow, amelioration of hepatic and ileal histopathology, and reduction of oxidative stress. In addition, paeoniflorin intervention restored EE-disrupted bile acid homeostasis in enterohepatic circulation. Further mechanism studies using western blot, quantitative Real-Time PCR, and immunohistochemical showed that paeoniflorin could upregulate hepatic efflux transporters expression but downregulate hepatic uptake transporter expression. Meanwhile, paeoniflorin reduced bile acids synthesis by repressing cholesterol 7α-hydroxylase in hepatocytes. Paeoniflorin affected the above transporters and enzyme via activation of a nuclear receptor, farnesoid X receptor (FXR), which was recognized as a vital regulator for maintaining bile acid homeostasis. In conclusion, paeoniflorin alleviated EE-induced cholestasis and maintained bile acid homeostasis via FXR-mediated regulation of bile acids transporters and synthesis enzyme. The findings indicated that paeoniflorin might exert a potential therapeutic medicine for estrogen-induced cholestasis.